2015
DOI: 10.1097/sla.0000000000001051
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Operating Room Distractions on Stress, Workload, and Teamwork

Abstract: Although some distractions may be inevitable in the OR, they can also be detrimental to the team. A deeper understanding of the effect of distractions on teams and their outcomes can lead to targeted quality improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
155
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(169 citation statements)
references
References 33 publications
11
155
0
3
Order By: Relevance
“…However, surgeons themselves also initiated the same. It was shown that irrelevant conversations negatively impact on teamwork 18. Higher stress was associated with acoustic distractions and equipment-related distractions, all negatively impacting team working ability.…”
Section: Barriers To An Effective Teammentioning
confidence: 99%
“…However, surgeons themselves also initiated the same. It was shown that irrelevant conversations negatively impact on teamwork 18. Higher stress was associated with acoustic distractions and equipment-related distractions, all negatively impacting team working ability.…”
Section: Barriers To An Effective Teammentioning
confidence: 99%
“…9 It has been validated and successfully utilized in multiple fields including transportation, energy, construction, education, and healthcare. [10][11][12][13][14][15][16][17] The TLX is comprised of six subscales: demand (how much mental and perceptual activity was required), physical demand (how much physical activity was required), temporal demand (how hurried or rushed was the pace of the task), performance (how successful was the subject in accomplishing what they were asked to do), effort (how hard did the subject have to work to accomplish the level of performance), and frustration level (how insecure, discouraged, irritated, stressed, and annoyed was the subject). 8 All subscales range from 0 (very low) to 100 (very high), with the exception of Performance, where 0 is perfect and 100 is failure.…”
Section: Study Outcome and Statistical Analysismentioning
confidence: 99%
“…[1][2][3] It has been postulated that there is a dynamic, cascading relationship between adverse factors that contribute to surgeons' stress levels. 4 That is, increased intraoperative workload can contribute to heightened cognitive demand, which can eventually surpass the surgeon or team's stress-coping ability, ultimately leading to excessive stress. In a recent survey of surgeons' experience managing intraoperative stressors, we found that 40% of responding surgeons had witnessed a technical complication resulting from the primary surgeon experiencing heightened stress.…”
Section: Introductionmentioning
confidence: 99%